2020
DOI: 10.4269/ajtmh.19-0954
|View full text |Cite
|
Sign up to set email alerts
|

Artemether–Lumefantrine Efficacy for the Treatment of Uncomplicated Plasmodium falciparum Malaria in Choco, Colombia after 8 Years as First-Line Treatment

Abstract: Artemether-lumefantrine (AL) is the first-line treatment for uncomplicated Plasmodium falciparum infection in Colombia. To assess AL efficacy for uncomplicated falciparum malaria in Quibdo, Choco, Colombia, we conducted a 28-day therapeutic efficacy study (TES) following the WHO guidelines. From July 2018 to February 2019, febrile patients aged 5-65 years with microscopy-confirmed P. falciparum mono-infection and asexual parasite density of 250-100,000 parasites/μL were enrolled and treated with a supervised 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…This combination, used in the country since 2006, has shown efficacy rates > 95% in different endemic areas. [8][9][10][11] However, it is important to emphasize that circulating P. falciparum parasites have previously shown a propensity to develop drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…This combination, used in the country since 2006, has shown efficacy rates > 95% in different endemic areas. [8][9][10][11] However, it is important to emphasize that circulating P. falciparum parasites have previously shown a propensity to develop drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study show that the parasite density criterion is not really a relevant criterion for the definition of severe cases in Colombia, since the low levels of parasitemia observed in this large number of patients with severe malaria are similar to the levels found in patients with uncomplicated malaria [36,37]. Therefore, parasite density should certainly not be used to make a clinical decision about the severity of the disease.…”
Section: Plos Onementioning
confidence: 77%
“…The stratification and description of S4 showed that there are few municipalities with a predominance of P. falciparum transmission that are located in the Pacific region. This is an opportunity to prioritize these areas to implement strategies to start eliminating transmission of this parasite in Colombia [54]. On the other hand, municipalities with P. vivax transmission are distributed throughout ecoepidemiological regions, and the elimination of this parasite species represents a challenge to malaria elimination due to the presence of mature gametocytes at an early stage of infection, resulting in greater transmissibility and relapse by the activation of dormant hypnozoites [55][56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…falciparum transmission that are located in the Pacific region. This is an opportunity to prioritize these areas to implement strategies to start eliminating transmission of this parasite in Colombia [ 54 ]. On the other hand, municipalities with P .…”
Section: Discussionmentioning
confidence: 99%